2020
DOI: 10.3390/ijms21176423
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Roles of ATP and Adenosine in Cholinergic Neuromuscular Transmission

Abstract: A review of the data on the modulatory action of adenosine 5’-triphosphate (ATP), the main co-transmitter with acetylcholine, and adenosine, the final ATP metabolite in the synaptic cleft, on neuromuscular transmission is presented. The effects of these endogenous modulators on pre- and post-synaptic processes are discussed. The contribution of purines to the processes of quantal and non-quantal secretion of acetylcholine into the synaptic cleft, as well as the influence of the postsynaptic effects of ATP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…TNAP regulates purinergic transmission in the central nervous system, and plays an important role in neuronal development, differentiation, and synaptic function [ 41 ]. TNAP inhibition also increases extracellular ATP in neurons, which can reduce motoneuron neurite extension [ 42 ], and dysregulate synaptic transmission in neuromuscular junction [ 43 ]. In addition, TNAP deficiency leads to reduced brain white matter, accompanied by decreased axonal myelination in the spinal cord and cortex [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNAP regulates purinergic transmission in the central nervous system, and plays an important role in neuronal development, differentiation, and synaptic function [ 41 ]. TNAP inhibition also increases extracellular ATP in neurons, which can reduce motoneuron neurite extension [ 42 ], and dysregulate synaptic transmission in neuromuscular junction [ 43 ]. In addition, TNAP deficiency leads to reduced brain white matter, accompanied by decreased axonal myelination in the spinal cord and cortex [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if Ang II is interstitially present, it does not affect acetylcholine releasing nerve terminal. However, ATP is likely the endothelial paracrine mediator [13], inhibiting cholinergic nerve endings [72].…”
Section: ) Only a Vascular Antagonist Blocks Vascular Agonist Effects While Interstitially The Antagonist Has No Actionmentioning
confidence: 99%
“…Through selective autocrine and paracrine signaling, these compartments alter each other diverse functions; "the response." The integration of this biophysical compartmentalization is far from a clear understanding [59], [60], [62], [63], [64], [71], [72].…”
Section: An Updated Model For Endocrine Actions Onmentioning
confidence: 99%
“…It is known that, at motor nerve terminals, ATP/adenosine diphosphate (ADP) as well as adenosine regulates neurotransmitter release when activating presynaptic inhibitory and facilitatory P2 and P1 Rs, respectively (Correia‐de‐Sá et al, 1996; De Lorenzo et al, 2004, 2006; Giniatullin & Sokolova, 1998; Salgado et al, 2000; Sebastião & Ribeiro, 2000; Sokolova et al, 2003; reviewed by Ziganshin et al, 2020). At the mouse NMJs, we have previously found that the cholinergic release is modulated by activation of inhibitory P2Y 13 Rs (De Lorenzo et al, 2006; Guarracino et al, 2016; Veggetti et al, 2008), A 1 Rs and A 3 Rs (Cinalli et al, 2013; De Lorenzo et al, 2004), and excitatory A 2A Rs (Palma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%